Deep space debris—Detection of potentially hazardous asteroids and objects from the southern hemisphere - Kruzins, Ed; Benner, Lance; Boyce, Russell; Brown, Melrose; Coward, David; Darwell, Sam; Edwards, Phil; Elizabeth-Glina, Lauren; Giorgini, Jon; Horiuchi, Shinji; Lambert, Andrew; Lazio, Joseph; et al. (Frontiers in Space Technologies, 2023)
Space debris are composed of both natural and human made objects, some in near Earth orbits while others are passing through deep space. Asteroids may represent one form of near Earth and deep space debris. In this article we report on a set of asteroid observations from the southern hemisphere that are classed as potentially hazardous asteroids (PHA’s) to orbiting spacecraft and Earth based facilities. Space agencies and institutions have observed and monitored near Earth asteroids and objects (NEO’s) using radio frequency antennas and optical telescopes in the northern hemisphere. A regular operational system to monitor the southern skies does not have the same level of maturity. The Southern Hemisphere Asteroid Radar Program (SHARP) located in Australia, uses available antenna time on either a 70m or 34m beam waveguide antenna located at the Canberra Deep Space Communication Complex to transmit a radio beam toward the NEO and receive its echoes at the 64m Parkes or 6x22m Australia Telescope Compact Array antennas at Narrabri in Australia. This mode of NEO observation is termed a deep space bistatic radar. Combining bistatic radar with small optical apertures allows combined optical/RF NEO detections. Whilst sub-metre class optical instruments have contributed independently to asteroid detection over decades, the use of coordinated small 0.3-0.5m instruments synchronized to large asteroid radars offers an observational flexibility and adaptability. Since 2015, SHARP has illuminated and tracked over 30 NEO’s ranging in diameter from 7m to 5000m at ranges of 0.1 to 18 lunar distances (LD) from Australia.